Fibrinogen: connecting the blood circulatory system with CNS scar formation - Conforti, Pasquale; Martínez Santamaría, Jose C.; Schachtrup, Christian (Frontiers in Cellular Neuroscience, 2024)
Wound healing of the central nervous system (CNS) is characterized by the classical phases of 'hemostasis', 'inflammation', 'proliferation', and 'remodeling'. Uncontrolled wound healing results in pathological scar formation hindering tissue remodeling and functional recovery in the CNS. Initial blood protein extravasation and activation of the coagulation cascade secure hemostasis in CNS diseases featuring openings in the blood-brain barrier. However, the relevance of blood-derived coagulation factors was overlooked for some time in CNS wound healing and scarring. Recent advancements in animal models and human tissue analysis implicate the blood-derived coagulation factor fibrinogen as a molecular link between vascular permeability and scar formation.In this perspective, we summarize the current understanding of how fibrinogen orchestrates scar formation and highlight fibrinogen-induced signaling pathways in diverse neural and non-neural cells that may contribute to scarring in CNS disease. We particularly highlight a role of fibrinogen in the formation of the lesion border between the healthy neural tissue and the fibrotic scar. Finally, we suggest novel therapeutic strategies via manipulating the fibrinogen-scar-forming cell interaction to improve functional outcomes.